A full Ka band gap waveguide based slot array antenna with 45° slant polarization - Zarifi, Davood; Farahbakhsh, Ali; Mrozowski, Michal (Scientific reports, 2025)
This work focuses on the development of a very wideband, 45° slant-polarized, 8 × 8-element slot antenna array for Ka-band applications. The proposed antenna utilizes gap waveguide to suppress undesired electromagnetic energy leakage and ensure high gain and efficiency. In the proposed design, the radiating slots are rotated by 45°, and a novel two-layer feed network implemented on the compact folded E-plane groove gap waveguide power dividers is used to excite the slots. An 8 × 8-element array prototype is designed, fabricated, and tested. Experimental results indicate that the proposed antenna array achieves a reflection coefficient better than − 10 dB and a peak gain of 26.9 dB across the full Ka-band bandwidth of 26.35 to 40 GHz. Due to the low-loss characteristics of gap waveguide technology, the antenna array exhibits high gain and efficiency. Additionally, the measured sidelobe level (SLL) and cross-polarization discrimination (XPD) are better than − 24.1 dB and 25.6 dB, respectively. The main advantages provided by the proposed E-plane groove gap waveguide-base antenna array with 45° Slant Polarization are low-profile, low-loss, wide bandwidth and usability at mm Wave frequencies.